Programming ColdFusion - Brooks-Bilson, Rob (O'Reilly & Associates, 2001)
Demonstrates the creation of dynamic Web applications while explaining how to use ColdFusion's tag-based language to process form data, query databases, share application data, create custom tags, and call external objects.